Humankind and the Cosmos: Early Christian Representations - ,Costache, Doru, (Vigiliae Christianae, Supplements ;, 2021)
In this volume, Costache endeavours to map the world as it was understood and experienced by the early Christians. Progressing from initial fears, they came to adopt a more positive view of the world through successive shifts of perception. This did not happen overnight. Tracing these shifts, Costache considers the world of the early Christians through an interdisciplinary lens, revealing its meaningful complexity. He demonstrates that the early Christian worldview developed at the nexus of several perspectives. What facilitated this process was above all the experience of contemplating nature. When accompanied by genuine personal transformation, natural contemplation fostered the theological interpretation of the world as it had been known to the ancients.